Effect of Steel Fibers on the Behavior of Over-Reinforced Beams Subjected to Pure Torsion - Gunneswara Rao T.D.; Rama Seshu D.; Warnitchai P. (Civil Engineering Dimension, 2010)
The improvement in torsional properties of reinforced concrete (RC) is becoming extremely important in the modern day constructions. Over the years the steel fiber reinforced concrete (SFRC) is being used for improving cracking characteristics of RC. The present paper deals with the behaviour of over reinforced SFRC members subjected to pure torsional loading. Torsion tests on the 15 reinforced steel fiber reinforced concrete beams revealed that, fiber has noticeable effect on the cracking torque and very little effect on the ultimate torsional strength of the member. However fiber inclusion could improve the torsional toughness of the member.